Compounded Oppressions and Intersections of Identities in Nottage’s Sweat - Paudyal, Janak (Bon Voyage, 2019)
Intersectionality has become the primary analytic tool in feminist and anti-racist scholarship to understand identity and oppression. This article critically interrogates the assumptions of intersectionality while underpinning white man’s supremacy and privilege in order to focus on the oppressed position of immigrant, African-American, and menial workers. In Lynn Nottage’s Sweat the white people enjoy the privileged position by belittling the underdogs. The social components like class, gender, race, and their discursive techniques work together to form and consolidate such an oppressed position. While looking from the perspective of feminism, this article encapsulates the equation mediated by multiple identity locations intersecting each other. The result of such an intersection of class, race and gender produces compound oppression which is the stigma of American democracy.